2019
DOI: 10.1093/scan/nsz051
|View full text |Cite
|
Sign up to set email alerts
|

A scent of romance: human putative pheromone affects men’s sexual cognition

Abstract: Previous studies suggest that the putative human pheromone estratetraenol affects several systems underlying human functioning and appears to activate neural systems that are known to affect sexual behavior. In this study, we investigated whether exposure to estratetraenol affects men’s social cognition abilities. In the first experiment, men performed the Interpersonal Perception task while being exposed to estratetraenol and to a control solution. Men performed the task with better accuracy while being expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…In rodents, female body odors stimulate the male reproductive system and induce increased sexual arousal (Richardson et al, 2004). The present finding that estratetraenol induces preference for large sexual rewards is consistent with the growing literature that estratetraenol, a putative human sex pheromone, increases sexual motivation among heterosexual males (Oren et al, 2019). In particular, when viewing photos with two humans either romantically touching or not, estratetraenol increased individuals' perceived emotionality of romantically touching, suggesting that estratetraenol conveys mating-related information such as the presence of women and their reproductive readiness.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In rodents, female body odors stimulate the male reproductive system and induce increased sexual arousal (Richardson et al, 2004). The present finding that estratetraenol induces preference for large sexual rewards is consistent with the growing literature that estratetraenol, a putative human sex pheromone, increases sexual motivation among heterosexual males (Oren et al, 2019). In particular, when viewing photos with two humans either romantically touching or not, estratetraenol increased individuals' perceived emotionality of romantically touching, suggesting that estratetraenol conveys mating-related information such as the presence of women and their reproductive readiness.…”
Section: Discussionsupporting
confidence: 91%
“…Previous evidence has suggested a link between estratetraenol and human reproductive function. In particular, exposure to estratetraenol affects self-reported sexual arousal and cognition among males (Oren et al, 2019). Furthermore, estratetraenol communicates gender information such that exposure to estratetraenol biases heterosexual males towards perceiving individuals as more feminine (Zhou et al, 2014) and primes the identification of emotionally receptive states for potential mates (Ye et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, heterosexual men enhanced their perception that female (but not) male stimuli were happier and more relaxed in the presence of EST than when these subjects smelled only a control masking odor, clove oil. 144 In another study by the same group 145 exposing men to EST enhanced their cooperative behavior in a competitive task-a trait the authors speculated would enhance males' attractivity to potential female mates. 132 In one recent study, men exposed to pharmacological concentrations of EST in a masking odor, but not to the masking odor alone, were both more accurate in judging interpersonal relationships and experienced a greater emotional response to photos of two people touching.…”
Section: Putative Female Pheromonesmentioning
confidence: 99%
“…132 In one recent study, men exposed to pharmacological concentrations of EST in a masking odor, but not to the masking odor alone, were both more accurate in judging interpersonal relationships and experienced a greater emotional response to photos of two people touching. 144 In another study by the same group 145 exposing men to EST enhanced their cooperative behavior in a competitive task-a trait the authors speculated would enhance males' attractivity to potential female mates.…”
Section: Putative Female Pheromonesmentioning
confidence: 99%
“…In addition, another study has shown that EST is related to men's sexual arousal and sexual motivation [23,24]. Furthermore, EST may trigger change in men's social cognition, especially in sexually related situations [25]. These reports remind us that there is a link between women' back, chest odor and men's sexual desire.…”
Section: Introductionmentioning
confidence: 92%